Comparison of the performance of Tubex® TF, widalimmunodiagnostic assay and blood culture in diagnosis of enteric fever in a private tertiary care hospital Peshawar, Pakistan - Kamran Amir Khan; Sameed Ullah Qureshi; Shumaila Ehtisham (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To determine and compare the performance of TUBEX® TF, widal test & blood culture in the diagnosis of enteric fever. Methods: After approving with the ethical committee, we retrospectively identified patients presented with fever at Northwest General Hospital and Research Centre. Typhidot, Widal test and blood culture was performed as part of their evaluation from January 2018 to December 2018. SPSS 16 was used for data analysis. Results: Of the 241 patients, blood culture was positive for salmonella in 68(28.21%) and negative in 173(71.79%). In the culture positive group, TUBEX® TF was positive in 29(42.64%) and negative in 39(57.36%). Of these culture positive patients, Widal was positive in 25(36.76%) and negative in 43(63.24%). In patients with negative culture, TUBEX® TF was positive in 58(37.66%) and negative in 96(62.34%), Widal was positive in 77(44.5%) and negative in 96(55.5%). The positive predictive value of TUBEX® TF was 33.33% and the negative predictive value was 71.77%. The sensitivity of TUBEX® TF was 42.65% while specificity was 62.34%. The positive predictive value of Widal was 24.51% and the negative predictive value was 69.06%. The sensitivity of Widal was 36.76% while specificity was 55.49%. Conclusion: Sensitivity, specificity, positive predictive value and negative predictive value of TUBEX® TF and Widal test is very low as compared to blood culture. Keywords: Enteric Fever, TUBEX® TF, Widal, Continuous...